2017
DOI: 10.4049/jimmunol.1600083
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Naive CD8 T Cell Response Features by Ligand Density, Affinity, and Continued Signaling via Internalized TCRs

Abstract: T cell response magnitudes increase with increasing antigenic dosage. However, it is unclear whether ligand density only modulates the proportions of responding ligand-specific T cells or also alters responses at the single cell level. Using brief (3 h) exposure of TCR-transgenic mouse CD8 T cells in vitro to varying densities of cognate peptide-MHC ligand followed by ligand-free culture in IL-2, we found that ligand density determined the frequencies of responding cells but not the expression levels of the ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 74 publications
(83 reference statements)
3
23
0
Order By: Relevance
“…25 Sorted B220+ and CD90+ cells were CFSE labelled and cultured on BMDC monolayers. 25 Sorted B220+ and CD90+ cells were CFSE labelled and cultured on BMDC monolayers.…”
Section: Motility Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…25 Sorted B220+ and CD90+ cells were CFSE labelled and cultured on BMDC monolayers. 25 Sorted B220+ and CD90+ cells were CFSE labelled and cultured on BMDC monolayers.…”
Section: Motility Assaymentioning
confidence: 99%
“…Bone-marrow-derived dendritic cells (BMDCs) were cultured, as previously described. 25 Sorted B220+ and CD90+ cells were CFSE labelled and cultured on BMDC monolayers. Cells were rested in the incubator for 2 hr, and then images were taken on Nikon Zeiss microscope every 5 min for 2 hr.…”
Section: Motility Assaymentioning
confidence: 99%
“…In vitro studies have observed that reducing ligand affinity can decrease readouts of naive CD8 + T cell activation including calcium fluxes, kinase and transcription factor activity, surface receptor and cytokine expression, and proliferation5,11,13–23. Similarly, changing ligand concentration or costimulatory signals can affect T cell activation11,16,21,24–28. However, T cell activation assays differ between studies, with some reported as analog and others digital with respect to ligand affinity3,4,17,18,21,23,27,29,30.…”
mentioning
confidence: 99%
“…The mechanisms causing variability in homogeneous naive T‐cell populations are likely to be a mixture of the stochastic and the environmentally induced. We have previously reported that cell population variation in glucose metabolism and rate of protein synthesis could be involved in regulating the variation in the ability of CD8 T cells to respond to TCR‐mediated stimulation . Recent reports have traced the in vivo CD8 T‐cell response at single‐cell level, demonstrating that there is a strong heterogeneity in the numerical output of clonal expansion from individual T cells .…”
Section: Discussionmentioning
confidence: 99%
“…In the immune system, with respect to naive T cells, stochastic fluctuations in gene expressions of regulators of T‐cell receptor (TCR) signaling such as extracellular signal‐regulated kinase (ERK) kinases have been linked to the ability of T‐cell clones to sense differences in ligand affinities . We have recently shown that variation in baseline glucose uptake and rates of protein synthesis in naive T cells regulate their ability to respond to TCR‐mediated stimulation . Also, variation in expression of Src‐homology‐2 domain containing protein tyrosine phosphatases, which provides a negative feedback loop for TCR signaling, has been shown to regulate T‐cell sensitivity …”
Section: Introductionmentioning
confidence: 99%